Simple, rapidly electroassembled thiolated PEG‐based sensor interfaces enable rapid interrogation of antibody titer and glycosylation. Issue 7 (3rd May 2021) - Motabar, Dana; Li, Jinyang; Wang, Sally; Tsao, Chen‐Yu; Tong, Xin; Wang, Lai‐Xi; Payne, Gregory F.; Bentley, William E.
Abstract: Process conditions established during the development and manufacture of recombinant protein therapeutics dramatically impacts their quality and clinical efficacy. Technologies that enable rapid assessment of product quality are critically important. Here, we describe the development of sensor interfaces that directly connect to electronics and enable near real‐time assessment of antibody titer and N‐linked galactosylation. We make use of a spatially resolved electroassembled thiolated polyethylene glycol hydrogel that enables electroactivated disulfide linkages. For titer assessment, we constructed a cysteinylated protein G that can be linked to the thiolated hydrogel allowing for robust capture and assessment of antibody concentration. For detecting galactosylation, the hydrogel is linked with thiolated sugars and their corresponding lectins, which enables antibody capture based on glycan pattern. Importantly, we demonstrate linear assessment of total antibody concentration over an industrially relevant range and the selective capture and quantification of antibodies with terminal β‐galactose glycans. We also show that the interfaces can be reused after surface regeneration using a low pH buffer. Our functionalized interfaces offer advantages in their simplicity, rapid assembly, connectivity to electronics, and reusability. As they assemble directly onto electrodes that also serve as I/O registers, we envision incorporation into diagnostic platforms including those in manufacturing settings. Abstract : In this study, we developed sensor interfaces for titer and N‐linked galactosylation detection that produce electrochemical outputs from electrodes upon which the sensing domains are also electroassembled. Unlike traditional analytical chemistry methods, our interfaces couple electrochemical techniques with biological molecular recognition elements. Importantly, we demonstrate linear assessment of total antibody concentration over an industrially relevant range and the selective capture and quantification of antibodies with terminal β–galactose glycans.